Methodology assessment for the design and analysis of aero-engine short intakes - Boscagli, Luca; Christie, Robert; MacManus, David G. (Council of European Aerospace Societies (CEAS), 2020)
A key aspect for the design of an aero-engine intake is that it must operate at off-design conditions such as high incidence. For short intake design the interaction with the fan cannot be neglected. This work establishes how different modelling strategies can affect the intake design boundaries and the analysis of an aero-engine short-intake. Unsteady simulations showed high levels of total pressure and swirl fluctuations while steady computations showed some limitations whenever extreme operating conditions are modelled. The analysis of a short intake showed that the fan is able to extend the incidence limit to avoid separation by about 0.6°. Overall, this work proposes a robust methodology for short-intake analysis
Keywords: unsteady; flow distortions; fan coupling; short intake